2014
DOI: 10.1055/s-0034-1377966
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound-guided placement of plastic vs. biflanged metal stents for therapy of walled-off necrosis: a retrospective single-center series

Abstract: Plastic stents and BFMS were safe and effective for the treatment of WON. In particular,BFMS placement appeared to be preferable for initial EUS-guided drainage and additional reintervention(e.g. DEN) as it reduced the procedure time. Prospective randomized controlled trials are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
153
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 102 publications
(160 citation statements)
references
References 16 publications
5
153
1
1
Order By: Relevance
“…Differences in treatment outcomes between the two studies may be explained by the significant heterogeneity in the data as a result of inclusion of unmatched patients in the previous study and the type of metal endoprostheses that were used. Although it is logical to assume that larger‐caliber metal stents will provide better drainage of necrotic contents and improve treatment outcomes, as with pseudocysts, we did not observe any difference, which is in line with a systematic review that demonstrated pooled treatment success rates of 70% and 78% (no significant difference) for the plastic and metal stent cohorts, respectively, as well as a recently published comparative study …”
Section: Discussionsupporting
confidence: 90%
“…Differences in treatment outcomes between the two studies may be explained by the significant heterogeneity in the data as a result of inclusion of unmatched patients in the previous study and the type of metal endoprostheses that were used. Although it is logical to assume that larger‐caliber metal stents will provide better drainage of necrotic contents and improve treatment outcomes, as with pseudocysts, we did not observe any difference, which is in line with a systematic review that demonstrated pooled treatment success rates of 70% and 78% (no significant difference) for the plastic and metal stent cohorts, respectively, as well as a recently published comparative study …”
Section: Discussionsupporting
confidence: 90%
“…This higher initial cost may be offset by shorter procedure times, but direct studies comparing LAMS and DPS overall costs for PFC are limited. 16,29 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the studies using metal stents included small number of patients. More recent studies display excellent outcomes with less technical difficulty or procedure duration while using novel metal stents in PFCs[53,55]. This is especially important in sick patients and when there is high likelihood of re-intervention for debridement or necrosectomy.…”
Section: Choice Of Stent - Metal or Plasticmentioning
confidence: 99%